Patterns of botulinum toxin treatment for spasticity and bleeding complications in patients with thrombotic risk. (November 2017) - Phadke, Chetan P.; Thanikachalam, Vivekanand; Ismail, Farooq; Boulias, Chris
Abstract: The purpose of this study was to assess the prevalence of compartment syndrome or major bleeding episodes and compare compartment syndrome, patient and intervention characteristics in 110 patients with stroke (treated with Warfarin, new oral anticoagulants, antiplatelet, or no anticoagulants) treated for spasticity in deep leg compartment muscles with botulinum toxin injections [onabotulinumtoxinA (n = 77); incobotulinumtoxinA (n = 33)]. We reviewed 674 injection cycles (range 1–25 cycles per patient) and found no cases of compartment syndrome in any patient groups. Highlights: We found no major bleeding in the deep compartment muscles with spasticity in anticoagulated patients on Warfarin. We found no major bleeding in the deep compartment muscles with spasticity in patients on new anticoagulants. Botulinum injection characteristics were not significantly different in patients with different types of anticoagulants. We found no major bleeding in the deep compartment muscles with spasticity in non-anticoagulated patients. We found no major bleeding in the deep compartment muscles with spasticity in patients receiving antiplatelet medications.